Renang Gaya Bebas 50 Meter Ditinjau Dari Kekuatan Otot Lengan Atlet Garuda Laut Usia 10 Tahun - Siti Nurhalizah Mutia Aulria (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This research aims to analyze the relationship between arm muscle strength and 50-meter freestyle swimming speed in Garuda Laut athletes aged 10 years. The research method used is quantitative with a correlational approach. Total sampling was conducted on 15 Garuda Laut athletes aged 10 years. Research instruments consisted of the Push-Up Test to measure arm muscle strength and a 50-meter freestyle swimming test with time measurement. Data analysis used descriptive statistics, normality test, Pearson correlation test, and simple linear regression test. The results showed a significant relationship between arm muscle strength and 50-meter freestyle swimming speed with a correlation value of r = -0.783 (p < 0.05). The contribution of arm muscle strength to 50-meter freestyle swimming speed was 61.3%. This research concludes that arm muscle strength is an important factor affecting 50-meter freestyle swimming speed in early age athletes. Training programs focusing on strengthening arm muscles are recommended to improve freestyle swimming performance in 10-year-old athletes.